A new species of Calluella Stoliczka, 1872 (Anura: Microhylidae) from Taman Negara, Pahang State, Peninsular Malaysia - Das, I.; Norsham, Yaakob; Liat, Lim Boo (National University of Singapore, 2004)
A new species of microhylid of the genus Calluella Stoliczka, 1872, is described from Sungai Relau, Taman Negara, Pahang State, Peninsular Malaysia. Calluella minuta, new species, is compared with congeners from Malaysia and other parts of south-east Asia. The new species is diagnosable in showing the following combination of characters: SVL 32.7 mm in the largest of the three specimens known; dorsum warty; no dermal fold across forehead; tympanum present; toe tips obtuse; webbing on toe IV broad up to median subarticular tubercle, webbing reaching tip of all toes as narrow sheaths; outer metatarsal tubercle present; and dorsum yellowish-brown with darker variegations.